PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI - Chusnul khotimah (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2023)
The purpose of this study was to examine the effect of profitability, liquidity, and asset structure on the capital structure of consumer goods industrial sector companies listed on the IDX for the 2019-2020 period. Profitability is calculated by return on equity (ROE), liquidity is calculated by current ratio (CR), asset structure and capital structure is calculated by debt to equity ratio (DER). The object of research is the consumer goods industry sector listed on the Indonesia Stock Exchange with a sample of 37 companies taken through purposive sampling. Hypothesis testing in this study was carried out using multiple regression analysis. The results of the study through the t test showed that profitability, liquidity had a significant effect on capital structure, while asset structure had no significant effect on capital structure.